PERILAKU RUMAH TRADISIONAL JAWA "JOGLO" TERHADAP GEMPA - Yulianto P. Prihatmaji (Dimensi: Journal of Architecture and Built Environment, 2007)
Javanese traditional house is located on earthquake zone 3 (midlle level), it spread from Banyuwangi (on East direction) until Cirebon (on West direction). Refer to form and construction system, the Joglo type house look a master piece of Javanese traditional house. It has impression of weight construction with rong-rongan structure (core in frame system from umpak-soko guru-tumpang sari) as vertical structure system. When earthquake come, wood structure of-rongan of Joglo house as a core structure or core in frame, it's a restrain to lateral force and depending on flexibility, brakebility, stability, elasticity and hiperstaticity of material and construction. The foundation system has hinge character or roll, connection system of tongue and gully configuration of secondary column (soko emper) and main column (soko guru), rigidity of main column (soko guru) from multy beam frame (tumpangsari/brunjung) are unity as earthquake responsive building. The test result of structure model of rong-rongan by vibration of earthquake force from horizontal slip table, is showed application of load system on Javanese traditional house support to stability. It has require on high frequency and acceleration low to high. Test on a vibration with low frequency and acceleration low to high, the load system make more deformation to model. The result of research is showed the structure of traditional Javanese house is safe on earthquake zone 3 (if base founfation maked clamp system). Abstract in Bahasa Indonesia : Rumah tradisional Jawa terletak di daerah gempa III (gempa sedang), terhampar dari Banyuwangi sampai Cirebon. Rumah tradisional Jawa berwujud Joglo secara bentuk dan konstruksi dianggap sebagai master piece rumah tradisional Jawa, yang terkesan berat dengan struktur rong-rongan (umpak-soko guru-tumpang sari) sebagai penahan beban lateral. Apabila terjadi gempa struktur kayu rong-rongan rumah Joglo dipandang sebagai struktur inti (core in frame) yang akan menahan gaya lateral, didukung oleh fleksibilitas, redaman, stabilitas, elastisitas, daktilitas, kehiperstatisan kayu dan konstruksi. Sistem tumpuan yang bersifat sendi dan atau rol, sistem sambungan lidah alur, konfigurasi soko-soko emper terhadap soko guru dan kekakuan soko guru oleh tumpang sari/brunjung dipandang sebagai kesatuan sistem earthquake responsive building. Hasil pengujian model struktur rong-rongan terhadap getaran gaya gempa dengan horizontal slip table, menunjukkan bahwa sistem pembebanan yang diterapkan di rumah Joglo menyumbang kestabilan, pada gempa frekuensi tinggi dan akselerasi rendah-tinggi. Pada getaran gaya gempa berfrekuensi rendah dan akselerasi rendah-tinggi, sistem pembebanan membuat model lebih banyak mengalami deformasi. Hasil penelitian menunjukkan bahwa, struktur rumah Joglo aman untuk daerah zona gempa 3 (apabila sistem tumpuan dibuat jepit). Kata kunci: struktur joglo, konstruksi rong-rongan, sistem sambungan dan tumpuan, gaya gempa.